Ser/Thr/Tyr Protein Phosphorylation in the Archaeon Halobacterium salinarum—A Representative of the Third Domain of Life - Aivaliotis, Michalis; Macek, Boris; Gnad, Florian; Reichelt, Peter; Mann, Matthias; Oesterhelt, Dieter (PloS one, 2009)
In the quest for the origin and evolution of protein phosphorylation, the major regulatory post-translational modification in eukaryotes, the members of archaea, the "third domain of life", play a protagonistic role. A plethora of studies have demonstrated that archaeal proteins are subject to post-translational modification by covalent phosphorylation, but little is known concerning the identities of the proteins affected, the impact on their functionality, the physiological roles of archaeal protein phosphorylation/dephosphorylation, and the protein kinases/phosphatases involved. These limited studies led to the initial hypothesis that archaea, similarly to other prokaryotes, use mainly histidine/aspartate phosphorylation, in their two-component systems representing a paradigm of prokaryotic signal transduction, while eukaryotes mostly use Ser/Thr/Tyr phosphorylation for creating highly sophisticated regulatory networks. In antithesis to the above hypothesis, several studies showed that Ser/Thr/Tyr phosphorylation is also common in the bacterial cell, and here we present the first genome-wide phosphoproteomic analysis of the model organism of archaea, Halobacterium salinarum, proving the existence/conservation of Ser/Thr/Tyr phosphorylation in the "third domain" of life, allowing a better understanding of the origin and evolution of the so-called "Nature's premier" mechanism for regulating the functional properties of proteins.